2006
DOI: 10.1103/physrevc.74.014004
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent pion photoproduction on the deuteron in the first resonance region

Abstract: Incoherent pion photoproduction on the deuteron is studied in the first resonance region. The unpolarized cross section, the beam asymmetry, and the vector and tensor target asymmetries are calculated in the framework of a diagrammatic approach. Pole diagrams and one-loop diagrams with N N scattering in the final state are taken into account. An elementary operator for pion photoproduction on the nucleon is taken in various on-shell forms and calculated using the SAID and MAID multipole analyses. Model depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
55
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 41 publications
7
55
0
1
Order By: Relevance
“…We first establish our calculation procedures by showing that the available data of incoherent pion photo-production reaction on the deuteron can be described reasonably well. Our results are fairly consistent with those from the earlier works [32][33][34][35][36] on this reaction, as will be discussed later. Thus the developed calculation procedures can be used reliably to investigate the πNN final state interaction effects on the cross sections of neutrino-induced single pion production reactions on deuteron.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…We first establish our calculation procedures by showing that the available data of incoherent pion photo-production reaction on the deuteron can be described reasonably well. Our results are fairly consistent with those from the earlier works [32][33][34][35][36] on this reaction, as will be discussed later. Thus the developed calculation procedures can be used reliably to investigate the πNN final state interaction effects on the cross sections of neutrino-induced single pion production reactions on deuteron.…”
Section: Introductionsupporting
confidence: 83%
“…The importance of the np final-state interactions is demonstrated, in agreement with the results of Ref. [32][33][34][35][36].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…[1][2][3][4] where also references to earlier research can be found. This interest is partly due to the new generation of high-intensity and high duty-cycle electron accelerators, such as MAMI at Mainz and ELSA at Bonn (Germany), JLab at Newport News (USA), and MAX-Lab at Lund (Sweden) as well as laser backscattering facilities such as GRAAL at Grenoble (France) and LEGS at Brookhaven (USA)-for an experimental overview see Refs.…”
Section: Introductionmentioning
confidence: 99%